Environmental effects on free space earth-to-satellite optical link based on measurement data in Malaysia - Nor, Norhanis Aida M.; Islam, Md. Rafiqul; Al-Khateeb, Wajdi Fawzi Mohammed; Zabidi, Suriza Ahmad (2012)
FSO is a developing technology that has a great chance to compliment the traditional wireless communications and offer some inherent advantages compared to microwave links due to transmitting higher speed of data, easily deployment,and no license spectrum required. However, FSO is very vulnerable to the climatological phenomena such as fog, snow,rain, and haze that reduce the link availability. Most researches and studies are focusing on improving the FSO system for terrestrial link based on data in temperate region. Therefore, this paper is aiming to provide the feasibility analysis on performing FSO from earth to satellite in Malaysia as the performance of FSO is dependent on local weather conditions and in tropical region, the attenuations are dominant by rain and haze. The analysis is based on measurement of rain intensity, visibility and variation of optical free space signal level which has been done at Faculty of Engineering, International Islamic University (IIUM)Kuala Lumpur campus. From the terrestrial data, it will be scaled up for earth to satellite especially Low Earth Orbit (LEO) satellite and will be compared with calculated of FSO earth-tosatellite data. The analysis will determine the operability of FSO for long distance and as a benchmark for future design.